All Days 2010
DOI: 10.2118/131131-ms
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Simulation of Field Treatments Using Core Flood Data

Abstract: Core flood experiments are an integral part of the methodology for chemical selection and the optimisation of scale inhibitor treatments, providing information on formation damage, inhibitor return profile and the dynamic retention isotherm under post flush conditions (as a function of SI, brine, pH, rock matrix, T etc.). In the absence of formation damage, the comparative inhibitor returns are often used to select the chemical prior to field treatment. However, it is recognised that there can be significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Test 1 inhibitor release curve presented the expected inhibitor release trend reported in literature. Test 2, however, presented an atypical curve. Lithology of core sample for test 2 comprises less mineral variety than that of samples from test 1: In particular, no clay mineral was detected in core samples for test 2.…”
Section: Resultssupporting
confidence: 66%
“…Test 1 inhibitor release curve presented the expected inhibitor release trend reported in literature. Test 2, however, presented an atypical curve. Lithology of core sample for test 2 comprises less mineral variety than that of samples from test 1: In particular, no clay mineral was detected in core samples for test 2.…”
Section: Resultssupporting
confidence: 66%
“…During injection ( Figure 5) significantly higher retention of "apparent" inhibitor is recorded for assay by ICP (total P) with much lower retention when analysed by Hyamine (for polymer). Similarly in the PF stage, considerably higher apparent inhibitor concentrations are recorded based on ICP for total P. As described in previous works 22 the active inhibitor components are better determined the polymer assay content and such significant differences are not uncommon both in core studies and field returns. The differences relate to the presence of residual (non polymeric) reactive "P" containing components preferentially retaining onto the rock substrate.…”
Section: Si Retention and Returns -Summary Of Results And Interpretationmentioning
confidence: 65%
“…In SPE 131131 22 it was shown that oversaturation has a significant impact on the behaviour of core-flood derived isotherms, due to the highly reactive nature of the acid phosphonate used in this test. Injection of multiple pore volumes of main treatment resulted in considerable oversaturation or overloading of the core with chemical.…”
Section: Summary -Over Saturation Examplementioning
confidence: 99%
See 1 more Smart Citation